Screening and production of polyhydroxybutyrate (PHB) by bacterial strains isolated from rhizosphere soil of groundnut plants - Haliru Musa; Bolanle, Badmus Basirat; Farizul Hafiz Kasim; Dachyar Arbain (Penerbit Universiti Kebangsaan Malaysia, 2016)
Polyhydroxybutyrate (PHB) otherwise known as bioplastics are biodegradable materials that are accumulated in various microorganisms to serve as carbon and energy reservoirs and regarded as an attractive alternative to petroleum-derived plastics. Although research has been conducted on isolation of PHB-producing microorganisms from different ecological environments, few studies have been carried out on isolation of potential PHB-producing microorganisms from rhizosphere environment of groundnut plants, Arachis hypogaea which can be regarded as a good environment for the isolation of potential PHB-producing microorganisms. In the present study, a total of twenty-one (21) bacterial strains were primarily screened and isolated from rhizosphere soil of a groundnut plant. Four bacterial isolates with maximum PHB-producing potential upon screening using submerged fermentation were selected for further studies. The fermentation pattern of PHB production was studied using different nutrient sources. The influence of agitation on PHB production was also studied. Mannitol stimulated maximum (6.076a mg/mL) PHB production by Bacillus sp. 1; KNO3 used as a limiting nutrient induced best (5.728a mg/mL) PHB production by Citrobacter sp. and MgSO4.7H2O supported maximum (5.972a mg/mL) PHB production in Enterococcus sp. A low agitation speed of 150 rpm was found to support best (5.802a mg/mL) PHB production by Bacillus sp.1. Findings from this study indicated that the isolated bacterial strains have high PHB- producing potential. The need to explore other environment harbouring microbial strains with high PHB-producing potential is paramount to the discovery of bioplastics with improved properties for potential industrial applications.